Nickel sulfide, nickel phosphide and nickel carbide catalysts for bio-hydrotreated fuel production. (1st November 2017) - Phimsen, Songphon; Kiatkittipong, Worapon; Yamada, Hiroshi; Tagawa, Tomohiko; Kiatkittipong, Kunlanan; Laosiripojana, Navadol; Assabumrungrat, Suttichai
Highlights: Bio-hydrotreated fuels are produced from non-edible spent coffee oil. The catalytic activity of Ni-based catalysts follows the order NiS < NiP < NiC. Decarbonylation is the major reaction route for all catalysts except NiP. NiC and NiS are suitable catalysts for production of gasoline and diesel, respectively. The obtained bio-hydrotreated fuels comply with the commercial BHD standard. Abstract: A series of nickel catalysts i.e. nickel sulfide (NiS), nickel phosphide (NiP) and nickel carbide (NiC) was investigated for hydrotreating of spent coffee oil to produce bio-hydrotreated fuel (BHF). Catalytic tests were carried out at 375–425 °C and 20–40 bar of initial H2 pressure (before heating) with reaction time of 0–3 h. The activity of the catalysts are in the order of NiC > NiP > NiS; however NiC tended to promote cracking reaction resulting in high gasoline and gaseous yields. On the other hand, although NiS gives the lowest oil conversion, it is favorable to diesel yield with lowest methanation and cracking activity. Compared with decarboxylation (DCO2 ) and hydrodeoxygenation (HDO), decarbonylation (DCO) was the major route for deoxygenation of coffee oil for all the catalysts. The ratio of (DCO + DCO2 ) to HDO (as represented by Cn-1 /Cn ) decreased in the order NiS > NiC > NiP. Ketones as intermediate products (ca. 3 wt%) were detected in case of NiP. They could be generated via rearrangement of alcohol and keto-enol tautomerism. Significant amount of aromatics (4 wt%) with some isomerization products (0.9 wt%) can also be observed in NiS catalyzed liquid products while trace amount of these compounds were detected for NiP and NiC catalysts. Physiochemical analysis of the diesel fraction exhibited satisfactory properties. The density and kinematic viscosity were consistent with the specification of commercial bio-hydrogenated diesel, NExBTL. Since main products are straight chain hydrocarbons, high cetane index (>110) could be achieved.